Vibrational Spectroscopic, Thermophysical, And Structural Properties Of Two Antarctic Howardites: EET 87503 and QUE 97001 - Unsalan, Ozan; Altunayar-Unsalan, Cisem; Nogueira, Bernardo A.; Kaliwoda, Melanie; FAUSTO, RUI (Elsevier Ltd., 2025)
This study uses optical microscopy, Raman spectroscopy, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) to examine the Antarctic howardite meteorites EET 87503 and QUE 97001. DSC results revealed troilite phase transitions in EET and QUE at 146.66 and 147.50 °C, corresponding to 0.26 % and 0.13 % troilite content, respectively. TGA indicated minor weight loss (<1 %) in both samples, with EET showing 0.399 % and QUE 0.638 % weight loss upon heating up to 1200 °C. Raman spectroscopy confirmed the presence of key minerals, including enstatite, ferrosilite, diopside, forsterite, ilmenite, and anorthite, as well as, in the case of the QUE 97001 meteorite, monticellite, a rare magnesium-end-member silicate olivine type mineral, providing insights into the complex thermal and impact histories of these howardites. The present findings appear as a contribution to a better understanding of the mineralogy and thermal evolution of this type of meteorites, linking them to potential parent bodies such as asteroid 4Vesta.
Keywords: EET 87503; Howardite; Infrared and Raman spectroscopy; QUE 97001; Thermal analysis